Análise geoecológica da planície litorânea de Trairi - CE: subsídios ao planejamento e ordenamento territorial - Oliveira, Mariana Alexandre de (2022)
The coastal plain of the municipality of Trairi - CE presents a unique mosaic of landscape units composing a natural framework of recognized scenic beauty, however, they constitute environments of high environmental fragility and, consequently, high vulnerability to occupation. Despite this, in this portion of space, human actions currently developed have become a matter of concern due to their various environmental impacts. The disordered use and occupation of these environmental systems have, in turn, gradually affected the environmental balance, as well as the quality of life of local populations, and caused progressive transformations in the landscape. Given this context, and in order to better understand this reality, the present dissertation aims to analyze the landscapes of the coastal plain of Trairi in an integrated way, in a systemic and interdisciplinary approach based on the science of Landscape Geoecology, seeking to to carry out a diagnosis capable of supporting proposals for environmental planning and territorial planning. With regard to the methodological path, this research is guided by the proposal of Rodriguez e Silva (2016) comprising the phases of organization and inventory, analysis phase, diagnosis phase and prognostic phase. As a result of the geoecological analysis of the landscape, 8 geoecological units were identified in the coastal plain of Trairi, namely: coastal sea, beach and post-beach strip, mobile dune field, fixed and semi-fixed dunes, eolianites, fluviomarine plain, lowland river and coastal board. The delimitation and spatialization of these units, in turn, made it possible to prepare a subsequent integrated environmental diagnosis encompassing the natural, social and legal potential and limitations of the study area; whose main objective is to highlight the predominant forms of land use and occupation, and to present an analysis of the main impacts, effects and consequences for the environment. At the end of the work, it appears that in the study area, depending on the forms and use and occupation of the soil incompatible with the support capacity of environmental systems, several geoecological units demonstrate a pressing need for actions regarding the management and Territorial Planning. In this sense, proposals for action and intervention are presented with regard to spatial planning, in order to mitigate impacts and achieve sustainable local development. The present work also includes a proposal for zoning the coastal plain of Trairi, in order to meet the needs of protection, conservation and recovery of local natural resources.